2016
DOI: 10.1037/emo0000109
|View full text |Cite
|
Sign up to set email alerts
|

Using decision models to decompose anxiety-related bias in threat classification.

Abstract: Individuals with high levels of anxiety show preferential processing of threatening information, and this cognitive bias is thought to be an integral component of anxiety disorders. In threat classification tasks, this bias manifests as high-anxiety participants being more likely to classify stimuli as threatening than their low-anxiety counterparts. However, it is unclear which cognitive mechanisms drive this bias in threat classification. To better understand this phenomenon, threat classification data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 23 publications
2
37
1
Order By: Relevance
“…Indeed, these models have already been used to examine cognitive biases relating to threat processing and classification among subjects with high levels of self-reported trait anxiety [see Existing Computational Studies of Trait Anxiety; also Ref. (6164)].…”
Section: Computational Backgroundmentioning
confidence: 99%
“…Indeed, these models have already been used to examine cognitive biases relating to threat processing and classification among subjects with high levels of self-reported trait anxiety [see Existing Computational Studies of Trait Anxiety; also Ref. (6164)].…”
Section: Computational Backgroundmentioning
confidence: 99%
“…Behavioural models of perceptual decision making, like drift-diffusion modelling (DDM; Ratcliff and McKoon, 54 2008), have shown that prior expectations may bias the starting point of evidence accumulation such that we are 55 predisposed towards one conclusion over another before the decision process has even begun (Barbosa et al, 2017, 56 Mulder et al, 2012, Wiech et al, 2014, Dunovan et al, 2014, White et al, 2018, White et al, 2016. Prior 57 expectations have also been shown to increase the drift rate of evidence accumulation (Dunovan et al, 2014, White 58 et al, 2016 and may lower the threshold for awareness (De Loof et al, 2016).…”
Section: Introduction 28mentioning
confidence: 99%
“…Thus, pathogen-avoidant strategies are likely to err on the side of caution by targeting both people who pose a disease threat and those who are only heuristically perceived to pose a disease threat. Indeed, one mechanism by which anxiety may increase threat perceptions involves lowering the decision criteria used to classify ambiguous stimuli as threatening (White, Skokin, Carlos, & Weaver, 2016).…”
Section: The Social Cognition Of Pathogen Avoidancementioning
confidence: 99%